Augmented Reality for Health Education's Model to Children with ARI (Acute Respiratory Infection) Culture Based Through Family Center Care Approach - Nuning Dwi Merina; Lantin Sulystiorini; Peni Perdani Juliningrum; Ira Rahmawati; Eka Afdi Septiyono (NurseLine Journal, 2021)
Acute Respiratory Infection is the main problem that always consulted or hospitalization in health care facilities, especially in the child care room. This study aims to identified health education's model to children with ARI (Acute Respiratory Infection) culture based through Family Center Care approach. This method is choosen to indeep interview out at child room in Jember Balung Hospital on may - september 2020. The subjects of the study are amount of eight person involving six nurses and two person from the families of children with ARI. The instruments used by TANNAHILS MODEL. The researcher identified 4 themes as a result of the study then all the themes are explained based on the specific objectives of the study. All the themes have sub-themes with specific categories of meaning. The results from themes that is identified in the study of interviews with preventive health protection are that each parent is different. One of the results of interviews about educational media that are suitable for the prevention of ARI in children are more often done using without media or “lesan” only when certain conditions use leaflets if needed. However, along with current technological developments, educational media are modified as attractive as possible to increase children's interest, one of which is educational media in the form of Augmented Reality (AR).